Projeto e testes de um aerogerador de pequeno porte e de um sistema de medição de eficiência mecânica - Lopes, Alberto dos Santos (2011)
In this paper was developed a small scale wind turbine and a structure for performance testing. It was employed the BEM (Blade Element Momentum Theory) to developing, design, fabrication and tests of wind turbine and the measuring system, including the blades aerodynamic analysis which was tested, it respective loading, destructive test and performance forecast. It was considered the complete mechanical design of main components. It was defined the tests methodology involving the instruments specifications, bench tests, field experiments, collected data analysis and results exposition and discussion. In order to validate the manufactured structure and system, it was verified the aerodynamic performance of a small scale wind turbine with 490 W. The results were compared with those proposed by BEM theory. The constructed device allowed establishing an appropriate condition for bigger wind turbine rotor in the future and with more technological complexity.